Beyond "justification" : dimensions of epistemic evaluation - Alston, William P. (Cornell University Press, 2005)
"Much of the writing in Anglo-American epistemology in the twentieth century focused on the conditions for beliefs being "justified." In a book that seeks to shift the ground of debate within theory of knowledge, William P. Alston finds that the century-long search for a correct account of the nature and conditions of epistemic justification misses the point. Alston calls for that search to be suspended and for talk of epistemic justification to cease. He proposes instead an approach to the epistemology of belief that focuses on the evaluation of various "epistemic desiderata" that may be satisfied by beliefs."--Jacket